2017
DOI: 10.3389/fmicb.2017.00144
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Molecular Characteristics of Extended-Spectrum β-Lactamase Genes in Escherichia coli Isolated from Diarrheic Patients in China

Abstract: Background: The emergence and spread of antimicrobial resistance has become a major global public health concern. A component element of this is the spread of the plasmid-encoded extended-spectrum b-lactamase (ESBL) genes, conferring resistance to third-generation cephalosporins. The purpose of this study was to investigate the molecular characteristics of ESBL-encoding genes identified in Escherichia coli cultured from diarrheic patients in China from 2013 to 2014.Materials and Methods: A total of 51 E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 31 publications
9
23
0
Order By: Relevance
“…CTX-M-15-producing EAEC strains belonging to ST38 from India causing TD have been described previously, demonstrating that ST38 is a successful EAEC group (34,35); however, in our study, this ST was also found in ETEC strains. The ST5584 ETEC strain carrying the bla CTX-M-15 gene isolated from a traveler to China was not found among a collection of E. coli strains causing diarrhea in China, reported in a recent study (36). Different replicon type profiles (FIB/FII, K, and Y) were found in these three ST38 EAEC strains.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…CTX-M-15-producing EAEC strains belonging to ST38 from India causing TD have been described previously, demonstrating that ST38 is a successful EAEC group (34,35); however, in our study, this ST was also found in ETEC strains. The ST5584 ETEC strain carrying the bla CTX-M-15 gene isolated from a traveler to China was not found among a collection of E. coli strains causing diarrhea in China, reported in a recent study (36). Different replicon type profiles (FIB/FII, K, and Y) were found in these three ST38 EAEC strains.…”
Section: Discussionmentioning
confidence: 80%
“…CTX-M-27-producing E. coli ST131 strains have been described in several countries (40), and the bla CTX-M-27 gene has been detected in EPEC and EIEC strains isolated in China (36). This bla CTX-M-27 gene has also been detected in one EAEC strain isolated from surface water (41).…”
Section: Discussionmentioning
confidence: 94%
“…Finally, each sample was resolved by PFGE in a Chef-Mapper (Bio-Rad, United States) at 14°C, with a switch time 2.16 to 54.17 s at 6 V/cm for 18 h. Each DNA band visualized was considered as a unit length of linear plasmid. The approximate size of each plasmid was determined by comparing profiles with Xba I-digested DNA from Salmonella serotype Braenderup strain H9812 ( Bai et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…5 The ESBLs are carried on bacterial plasmids that can be transferred to other bacteria. 6 Several ESBL classes have been detected in Enterobacteriaceae strains of which the CTX-M, TEM, and SHV beta-lactamases are the most common types. 7 ESBL-PE are usually resistant to most beta-lactam antibiotics, however, carbapenems are considered the drugs of choice for treatment of infections caused by these bacteria.…”
Section: Introductionmentioning
confidence: 99%